The number of passively smoked cigarettes and the risk of lung cancer among the inhabitants of the Świętokrzyskie Region (2010-2018) - Chudzik, Robert; Rybojad, Paweł (Journal of Education, Health and Sport, 2021)
Air purity is one of the factors affecting human health. Over the years, numerous scientific reports have provided us with evidence of the effects of air pollution on health. Along with the increase in pollution, the risk of respiratory and circulatory diseases in particular increases. The main pollutants are Airborne particulate matters (PM) which, depending on the size, vary between 2.5 and 10. Their presence is mainly related to the burning of fossil fuels. Another significant air pollutant is NO2, mainly related to road transport. It is believed that the long term exposure to NO2 could increase inflammation. The negative effect of air pollution is also associated with an increased frequency of strokes, exacerbations of mental illnesses and also with diseases of the digestive system. We analyzed the data available in the Polish National Cancer Registry (PNCR), Chief Inspectorate for Environmental Protection and Air Quality Guidelines, We checked air pollution by the means of PM2.5 , PM10 and NO2 and thanks to mathematical equation delivered by Saskia C. van der Zee converted them into number of passively smoked cigarettes. Above data we compared to lung cancer morbidity in Świętokrzyskie Region. Based on the latest published data, we can infer that in 2010-2018 each citizen of Świętokrzyskie Region smoked average 9,8 cigarettes a day +/- 2,3. The incidence of lung cancer is more or less the same number with a slight upward trend. After 61 years everyone in the exanimated region had 30 package-years of passive smoking and high risk of lung cancer. Air quality in Poland is not rewarding, exceeding WHO Guidelines 2005 recommendations translates into an increased risk of respiratory and cardiovascular diseases.